Study of a Newly Discovered Microliths and Rock Art Site, Badedev Rakseha at Panna District of Madhya Pradesh, India. (31st January 2022) - Patel, Devideen; Farswan, Yogambar Singh
The literary data revealed that the Panna district of Madhya Pradesh has not been explored extensively in the context of prehistoric archaeology. Therefore, present study is considered, keeping in view for the same. For this purpose, a systematic exploration of Panna district was conducted during seasons 2019–20. After exploration, a rock art and microliths assemblage site, Badedev (24°45'41.80" N 80°17'2.73"E), Rakseha was discovered at Panna district by the first author and recovered around 500 Microliths assemblages and 02 rock shelters with depiction of paintings. The major type of microliths artefacts identified are; core, flake, blade, bladelets, scraper, lunate, borer, burin, points, triangle, and debris. The typo-technological and morphological analyses of assemblages revealed that various types of stone artefacts used by prehistoric group of this area were made on locally available raw material and they have a sound knowledge of durability of raw material used for tool making, as we have identified more than 36% and 30% of agate and quartz type of microliths respectively among the whole artifacts collected, as both of these are hard as well as durable type of stones. Remains of microliths assemblages and debitage stone material also certified that Badedev prehistoric site was a tool manufacturing site at this area. In rock paintings, themes are most dominantly zoomorphic figurine, human figurine, handprints, and geometric and non-geometric design. For detail study of pictographs DStretch software was utilized. On the basis of rock art style, color, composition, technique, theme, subject matter; motifs such as hunting scenes and large number of animal groups, it is assumed that this site was inhabited by hunter-gatherer group. Finally we are in position to say that the discovery of prehistoric site Badedev Rakseha enhanced our knowledge about the prehistoric culture of central Indian region.